2015
DOI: 10.1074/jbc.m115.668871
|View full text |Cite
|
Sign up to set email alerts
|

Role of Erk1/2 Signaling in the Regulation of Neutrophil Versus Monocyte Development in Response to G-CSF and M-CSF

Abstract: Background: G-CSF and M-CSF are cytokines that support the development of neutrophils and monocytes, respectively. Results: The duration of Erk1/2 activation by G-CSF and M-CSF affects the lineage commitment of myeloid precursors. Conclusion: G-CSF and M-CSF instruct neutrophil versus monocyte development through differential activation of Erk1/2. Significance: This reveals a key mechanism by which G-CSF and M-CSF control lineage specification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Due to the biological coupling of the disc with the bone marrow, these pro-inflammatory and pro-osteoclastic genes can also directly exert their myelopoietic effects in the bone marrow. For instance, IL-6 activates myelopoiesis while suppressing erythopoiesis 19,30 , IL-4 governs T helper cell 2 differentiation and is a potent neutrophilic maturation factor 31 , CSF1 instructs hematopoietic stem cells to differentiate along the myeloid lineage and supports neutrophil differentiation 32,33 , and CCL2 recruits monocytes/macrophages and myeloid progenitors 34 . It is therefore not surprising that myelopoiesis is dysregulated in MC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the biological coupling of the disc with the bone marrow, these pro-inflammatory and pro-osteoclastic genes can also directly exert their myelopoietic effects in the bone marrow. For instance, IL-6 activates myelopoiesis while suppressing erythopoiesis 19,30 , IL-4 governs T helper cell 2 differentiation and is a potent neutrophilic maturation factor 31 , CSF1 instructs hematopoietic stem cells to differentiate along the myeloid lineage and supports neutrophil differentiation 32,33 , and CCL2 recruits monocytes/macrophages and myeloid progenitors 34 . It is therefore not surprising that myelopoiesis is dysregulated in MC.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted us to investigate the mechanism of regulation of MTA1 transcription by G-CSF. Previous reports (33)(34)(35) have shown that c-Fos acts as a downstream effector transcription factor of STAT3 and MAPK signaling cascades upon G-CSF treatment. Sequence analysis of the MTA1 promoter revealed a putative c-Fos binding consensus sequence TGACT-CAC (36) at regions Ϫ2121 to Ϫ2114.…”
Section: Validation Of G-csf Effect In Acute Mptp Mousementioning
confidence: 93%
“…From the above results, it is clear that c-Fos is required for the G-CSF-induced activation of MTA1. Because c-Fos induction by G-CSF was reported to be mediated by the MAPK and STAT3 pathway (33)(34)(35), we looked at the activation status of both pathways and found that both pathways are activated upon G-CSF treatment (data not shown). Consistently, G-CSF failed to induce MTA1 promoter activity upon inhibiting STAT3 and MAPK pathways (data not shown).…”
Section: Validation Of G-csf Effect In Acute Mptp Mousementioning
confidence: 99%
“…18 A potential signaling pathway downstream of SFKs involved in lineage choice is the MEK/ERK pathway. 37,38 It has previously been shown that Y559 activates SFK and MEK/ERK signaling in Ms. 18 To test whether ERK is activated through Y559(/807) in primary progenitors, we performed phospho-flow with Csf1r 2/2 ivGMPs expressing Ywt, YEF, Y559AB, or Y559/807AB. Stimulation with CSF-1 led to ERK activation with both AB mutants and could be blocked using an SFK inhibitor, demonstrating that Y559 signals through MEK/ERK via SFKs ( Figure 5A-B).…”
Section: Y559 Signals Via Sfk-mek/erkmentioning
confidence: 99%